3D Fluid‐Structure Interaction Experiment and Benchmark Results. Issue 1 (25th October 2016) - Hessenthaler, Andreas; Friedhoff, Stephanie; Röhrle, Oliver; Nordsletten, David A.
Abstract: Testing and comparison of well‐known and recently developed numerical methods and algorithms are the key for their thorough assessment and continued improvement. We will present a short overview of a new 3D FSI experiment that proposes steady and dynamic test cases (referred to as Phase I and Phase II ), complementing well‐known standard benchmark problems. In this context, we discuss a mathematical FSI model, that has previously proofed capable of good predictions, and demonstrate that the periodic steady‐state solution for Phase II is insensitive to the initial deformation of the solid. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)